The Utilize of Tembang Macapat by Ki Ageng Selo As an Islamic Da’wah Media in Javanese Society of Selo Village, Grobogan, Indonesia - Moh Sayful Zuhri; Kundharu Saddhono; Sumarwati Sumarwati (Javanologi: International Journal of Javanese Studies, 2023)
The teaching of religion in each belief has its own characteristic. Various kinds of media and methods are used to invite someone to follow these religious thought. Islam is one of the largest following faiths in the world. The spread of Islam in Indonesia that is by way of marriage, trade and even with art. One of those arts is by using a traditional song, namely the tembang macapat. The people of Selo village, Grobogan at first had Hindhu-Buddhist beliefs and dynamism. The use of tembang macapat as an Islamic da’wah media attract the attention of the Javanese society in that village. The tembangmacapat was made by Ki Ageng Selo. The research method used is descriptive qualitative with ethnographic approach. The data were collected through the document analysis of tembang macapat and in-depth interviews with related sources. The results of this study revealed that there is a connection in the utilize of Ki Ageng Selo's tembang macapat as an Islamic da’wah media at that time. The song contains the Quran and hadiths in Islam. This study will be a message on the relationship between tembang macapat and culture in the community, especially in selo village, Grobogan.